P206 Achieving responsible oxygen prescribing to improve value: london care homes. (15th November 2016) - Lock, C; Gardner, M; Restrick, L; Williams, S; Buxton, M; Haastrup, M; Krishek, B; Mak, V; Roots, D; Patel, I
Abstract : Background: Around 85, 000 patients are currently prescribed home oxygen (HO) in England, costing the NHS > £100 million/yr. There are about 11000 HO users in London costing £12 million/yr. Department of Health data suggest 24%–43% of oxygen prescribed is not used/used inappropriately. The aim of this study was to better understand HO prescriptions/use in London nursing/care homes. Methods: Air Liquide (AL), the London oxygen provider, reviewed their database to identify nursing/residential/care home and hospice residents with an active HO Order Form (HOOF) as of January 2016. Staff education and support was undertaken by the AL respiratory nurse advisor (ALRNA) from Jan–June 2016. Results were reviewed with the London Clinical Oxygen Network. Results: 245 adult patients with a HO prescription were identified across 155 nursing/residential/care homes and hospices in London (mean age 77, range 22–102 years). Table 1 shows the Clinical codes on the HOOFs. The indication for oxygen was unknown in 52 (21%). HO prescription ranged from 0.5–15 LPM; equipment ranged from oxygen concentrators, ambulatory cylinders (89), static cylinders (22), portable oxygen concentrators (5) and liquid oxygen (2). 168 (68%) patients were underusing oxygen while 38 (15%) were overusing. 36 (14%) patients were not using their oxygen at all. Only 90 (36%) patients had a HOOF dating from 2016; 157 (64%) had a HOOF more than a year old. Issues noted included lack of information as to indication for HO and who to contact for guidance, absence of clinical directives from prescribers resulting in 'PRN' oxygen use and training needs around storage/use of oxygen equipment. Conclusion: A sizable number of nursing/residential/care home and hospice residents in London are currently prescribed oxygen which is being over/under or inappropriately used without ongoing specialist support/review. For 1 in 5 patients the clinical indication is unknown. New oxygen prescriptions for 'nursing home' patients should include guidance on use, staff training and ongoing support. These data exemplify broader issues relating to a lack of commissioned HO pathways and the need for commissioned Home Oxygen Review (HOS-R) services across all CCGs to keep patients safe, maximise patient benefit and reduce waste.